Methane emissions from fens in Alberta’s boreal region: Reference data for functional evaluation of restoration outcomes - Bienida, Aneta; Date, Vinay; Andersen, Roxane; Nwaishi, Felix; Price, Jonathan S.; Mahmood, Md. Sharif; Strack, Maria (Springer, 2020)
The aim of the study was to document methane (CH4) dynamics from fen ecosystems in the Athabasca Oil Sands Region (AOSR) in northern Alberta to create a reference database for evaluation of peatland restoration and reclamation projects in the region. The study included three types of fens commonly occurring in this region: poor fen (open and treed), moderately-rich treed fen, and open saline fen. We quantified CH 4 fluxes, pore water concentration (PW[CH 4]), and production potential together with ecohydrological variables that may influence CH4 dynamics over four growing seasons. Mean (standard deviation) fluxes for open and treed poor fen (99.8 (269.7) and 68.3 (118.8) mg CH4 m -2 d -1, respectively) were higher than for treed rich (32.8 (63.7) mg CH4 m -2 d -1) and open saline fens (34.6 (91.3) mg CH4 m -2 d -1). The total growing season CH4 emissions from these fens ranged between 3.7 and 11.3 g CH4 m -2. Methane production potential varied from 0.1 (0.1) µmol CH4 g peat -1 d -1 at the saline fen to 4.6 (0.8) µmol CH 4 g peat -1 d -1 at the treed rich fen. The variability of CH4 fluxes and pore water concentration between study sites and years was mostly controlled water table (WT) and soil temperature indicating that these variables should be used to assess the expected CH4 flux in peatland reclamation projects. Large inter-annual variability in CH4 flux illustrates the importance of multi-year records for data used in functional evaluation of restoration outcomes.
This is a post-peer-review, pre-copyedit version of an article published in Wetlands Ecology and Management. The final authenticated version is available online at: https://doi.org/10.1007/s11273-020-09715-2
Keywords: CH4; dissolved methane; ecological restoration; peatland; reclamation